Exploring the underexplored genus Chenopodium, a potentially neglected underutilized species from Manipur North Eastern Region of India - Devi, Rajkumari Jashmi; Thongam, Biseshwori (Current Botany, 2025)
The Northeastern region (NER) of the India is home to a rich diversity of plant species. Many of them are underexplored and nurtured by indigenous communities for their potential value to humankind. The genus Chenopodium of family Amaranthaceae is one of the neglected and underutilized plant species known for its higher content of protein, minerals, vitamins and abiotic stress tolerance. However, taxonomically this genus is known to be a complex genus due to the lack of good morphological characters that can distinguish species. This genus has around 132 accepted species worldwide. In the present study, we have briefly described four Chenopodium species viz. Chenopodium murale, C. ficifolium, C. giganteum and C. album from Manipur, India. Of these, three species viz. C. murale, C. ficifolium, and C. giganteum are new records from Manipur, India.